“O piso da cozinha”, de Audre Lorde - da Costa Moreira, Bruna Elisa (Rónai – Revista de Estudos Clássicos e Tradutórios, 2023)
LORDE, Audre. “Kitchen Linoleum”. In: ____. The collected poems of Audre Lorde, New York: W.W. Norton & Company, 2000, p. 452. Copyright © by Audre Lorde, Charlotte Sheedy Literary Agency & W.W. Norton & Company.